2018
DOI: 10.1186/s13099-018-0266-5
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in Enterobacteriaceae from healthy broilers in Egypt: emergence of colistin-resistant and extended-spectrum β-lactamase-producing Escherichia coli

Abstract: BackgroundPoultry remains one of the most important reservoir for zoonotic multidrug resistant pathogens. The global rise of antimicrobial resistance in Gram-negative bacteria is of reasonable concern and demands intensified surveillance.MethodsIn 2016, 576 cloacal swabs were collected from 48 broiler farms located in five governorates in northern Egypt. Isolates of Enterobacteriaceae could be cultivated on different media and were identified by MALDI-TOF MS and PCR. Escherichia coli isolates were genotyped by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
59
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 77 publications
14
59
2
Order By: Relevance
“…In the present study, the antibiograms of the Enterobacteriaceae isolates showed that all E. cloacae isolates ( n = 28) were resistant to amoxicillin, cefalotin, cefuroxime, cefoxitin and cefuroxime axetil while only one isolate was resistant to cefpodoxime. Similar to our findings, E. cloacae isolates from healthy broilers were reported to be resistant to amoxicillin [ 48 ] and those from green leafy vegetables were resistant to cephalothin, cefuroroxime, cefoxitin, amipicillin, and amoxicillin-clavulanate [ 49 ]. The increasing antibiotic resistance of pathogenic bacteria is a major public health issue as that will increase foodborne illnesses and narrow treatment choices [ 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the antibiograms of the Enterobacteriaceae isolates showed that all E. cloacae isolates ( n = 28) were resistant to amoxicillin, cefalotin, cefuroxime, cefoxitin and cefuroxime axetil while only one isolate was resistant to cefpodoxime. Similar to our findings, E. cloacae isolates from healthy broilers were reported to be resistant to amoxicillin [ 48 ] and those from green leafy vegetables were resistant to cephalothin, cefuroroxime, cefoxitin, amipicillin, and amoxicillin-clavulanate [ 49 ]. The increasing antibiotic resistance of pathogenic bacteria is a major public health issue as that will increase foodborne illnesses and narrow treatment choices [ 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…Also, 55 (66.3%) strains showed resistance (MIC ≥ 4 mg/L) to colistin. The high prevalence of colistin resistance and circulation of mcr-1 among the E. coli collected from this broiler farm was unexpected, as the occurrence of MCREC in avian farms is usually low, e.g., 10% in China ( Yang et al, 2017 ), 8% in Egypt ( Moawad et al, 2018 ), 2% in South Africa ( Perreten et al, 2016 ), and 2% in France ( Perrin-Guyomard et al, 2016 ). The exceptionally high detection rate of MCREC (63.9%) in the current study is worrying as distribution of mcr-1 along the broiler industry chain is possible ( Wang et al, 2017c ).…”
mentioning
confidence: 95%
“…Generally, the occurrence of colistin resistance and mcr-1 among Enterobacteriaceae isolates from humans (0.1%–8.8%) is lower than that from livestock (0.9%–76.9%) ( Liu & Liu, 2018 ; Liu et al, 2016 ; Quan et al, 2017 ; Wang et al, 2017b ). For avian species, the detection rate of Enterobacteriaceae carrying mcr-1 is generally below 30% ( Lentz et al, 2016 ; Moawad et al, 2018 ; Perrin-Guyomard et al, 2016 ; Shen et al, 2016 ; Trung et al, 2017 ). In China, the prevalence of mcr-1 and colistin resistance in E. coli from avians (~10%) is generally lower than that from swine (~30%) ( Huang et al, 2017 ; Yang et al, 2017 ; Zhang et al, 2018 ).…”
mentioning
confidence: 99%
“…The high prevalence of multidrug-resistant APEC poses a zoonotic risk in developing countries [ 8 , 9 , 10 ]. Therefore, alternatives such as vaccines and lectins are being developed to combat E. coli infection in poultry [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%